3D Rendering and Types of Mapping in Computer Graphics - Dobbins, Patria, author 640012; Badillo, Harriett, author 640013 (Delhi, India : World Technologies, 2012)
This book explains about 3D Rendering and Types of Mapping in Computer Graphics.